ESG Effects on Firm Value Through Financial Performance in Indonesian LQ45 Companies - Wahyul Huda Nanda; Erlina Erlina; Isfenti Sadalia (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the influence of Environmental, Social, and Governance (ESG) on firm value, with financial performance as a mediating variable in LQ45 companies listed on the Indonesia Stock Exchange. This research is motivated by increasing attention to corporate governance practices and inconsistencies in previous research regarding the relationship between ESG, financial performance, and firm value. In this study, the Environmental, Social, and Governance dimensions are viewed as strategic factors that can enhance corporate legitimacy, strengthen investor confidence, and drive increased firm value through financial performance. This study uses a quantitative approach with panel data analysis. The data used are secondary data obtained from financial reports, sustainability reports, and Sustainalytics ESG scores for LQ45 companies for the 2022–2024 period. Data analysis techniques used panel data regression and mediation tests to examine the direct and indirect effects between the study variables. The results indicate that Environmental, Social, and Governance influence firm value. Furthermore, ESG also influences firm financial performance. Furthermore, financial performance has been shown to mediate the relationship between ESG and firm value. These findings indicate that sound ESG implementation can increase profitability, strengthen a company's reputation, and enhance investor confidence, thus increasing its value. Therefore, companies need to optimize the implementation of ESG as a long-term business strategy to enhance their competitiveness and desirability in the Indonesian capital market.